2020
DOI: 10.1002/cjce.23734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of support on the apparent activity of palladium oxide in catalytic methane combustion

Abstract: The support effect on the low temperature catalytic oxidation of methane over palladium catalysts was studied by comparing a series of metal oxides as the support. Samples of 0.010 g/g Pd catalysts supported on different grades and/or phases of TiO2, Al2O3, and ZrO2 were prepared via incipient impregnation and their catalytic activity was evaluated using a laboratory plug‐flow reactor. The specific surface area of the supports determined by nitrogen adsorption varied from about 13‐220 m2/g. Initial experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…[109] These modifications also create vacancies in surface oxidative processes, which can enhance catalytic activity. [110] In this study, we observed improvements in the oxidation and reduction processes of oxygen in the catalyst, as evidenced by experimental results demonstrating higher mobility of coordinated oxygen atoms in each crystalline phase. [111] We compared this improvement to that of the PCZA catalyst, which Al +2 is commonly used for acetoxidation processes on PdAu (100) surfaces.…”
Section: Proposal Of a Reaction Mechanismsupporting
confidence: 55%
“…[109] These modifications also create vacancies in surface oxidative processes, which can enhance catalytic activity. [110] In this study, we observed improvements in the oxidation and reduction processes of oxygen in the catalyst, as evidenced by experimental results demonstrating higher mobility of coordinated oxygen atoms in each crystalline phase. [111] We compared this improvement to that of the PCZA catalyst, which Al +2 is commonly used for acetoxidation processes on PdAu (100) surfaces.…”
Section: Proposal Of a Reaction Mechanismsupporting
confidence: 55%
“…In the article [102], it is indicated that Pd on Al 2 O 3 support had a higher activity than Pd-Pt or Pd-Pt-Rh on the same support. Activity of Pd over alumina, zirconia, and anatase-support in [101] for the same temperature was different. Modification by Ca addition led to high oxygen mobility and strong Pd support interaction [82].…”
Section: Role Of Supportmentioning
confidence: 94%
“…Catalytic performance is strongly dependent on the nature of the support [75,95,101] and depends on the interaction between the support and active phases [81]. The comparison of the influence of additives in catalysts by various authors on a chemical reaction is not easy.…”
Section: Role Of Supportmentioning
confidence: 99%
“…[103] TiO 2 can improve metal dispersion due to its large specific surface area and potent affinity for noble metals. [104] Moreover, as sulfating support, Ti-containing catalysts display higher tolerance toward SO 2 and H 2 O. [105] Through an ultrasonic-assisted sol-gel method, Ti was introduced into an alumina carrier.…”
Section: Pd-based Catalystsmentioning
confidence: 99%